Rhabdomyolysis in Thyroid Crisis - Nanny Natalia Mulyani Soetedjo; Luse Loe; Maya Kusumawati; Ervita Ritonga; Hikmat Permana (Majalah Kedokteran Indonesia, 2022)
Introduction: Hyperthyroidism might lead to rhabdomyolysis. Rhabdomyolysis in thyroid crisis is very rare, currently there are only 7 cases in the world. This is the eight cases in the world that had been reported.Cases: We reported a case of a 46-year-old man with Graves’ Disease who presented with thyroid crisis and rhabdomyolysis.Discussion: The patient came with shortness of breath and palpitations for 10 hours before admission. Tachycardia, tachypnea, thyroid enlargement, motoric weakness, and bilateral lung crackles were noted. The Burch-Wartofsky Point Scale was 60 and the Japan Thyroid Association grade was TS2 first combination. Laboratory showed hyperkalemia (7.7 meq/L), increase in urea (144 mg/dl), creatinine (1.92 mg/dl), fT4 ( greater than 5.0), TSHs (0.06 uIU/ml) creatine kinase (3645 U/L), positive TRAb and Anti-TPO. The patient was treated with thyroid crisis management (propylthiouracil, lugol, dexamethasone) and supportive treatment (dobutamine, digoxin, furosemide, antibiotics, hyperkalemia therapy). After hospitalized for 11 days, the patient was discharged with resolution clinical symptom and levels of CK, urea, and creatinine. Conclusion: Hyperthyroidism might lead to rhabdomyolysis. This condition needs to be recognized and becomes a differential diagnosis in non-traumatic rhabdomyolysis accompanied by acute kidney injury. Therefore, can lead to appropriate and prompt management.